Structural and functional neuroimaging of hippocampus to study adult neurogenesis in long COVID-19 patients with neuropsychiatric symptoms: a scoping review - Jayakumar Saikarthik; Ilango Saraswathi; Bijaya Kumar Padhi; Muhammad Aaqib Shamim; Nasser Alzerwi; Abdulaziz Alarifi; Aravind P. Gandhi (PeerJ, 2025)
Background Worsening of neuropsychiatric and neurodegenerative disorders occurs in COVID-19. Impaired adult neurogenesis is linked to most of the neuropsychiatric symptoms and disorders. Aim The current scoping review identified and mapped the available evidence on adult neurogenesis in long COVID-19, at a global level following the JBI methodology for scoping reviews and followed the framework by Arksey and O’Malley. Method Original studies focusing on structural and functional neuroimaging of the hippocampus to study adult neurogenesis in long COVID-19 were included in the review. Studies published in English language with no restriction on the time of publication were searched using the specified search strategy in PubMed, Web of Science, Embase, and SCOPUS. Articles obtained from the database search were collated and uploaded into the Nested Knowledge AutoLit semi-automated systematic review platform for data extraction. Results The current review provides evidence of the potential alterations in adult neurogenesis in long COVID-19 and its potential link to neuropsychiatric sequelae of long COVID-19, with further research required to validate this assertion. Conclusion This review proposes conceptual and methodological approaches for future investigations to address existing limitations and elucidate the precise role of adult neurogenesis in the pathophysiology and treatment of long COVID-19.